Commercial Aircraft Selection Decision Support Model Using Fuzzy Combinative Multiple Criteria Decision Making Analysis - Ardil, Cemal (Journal of Sustainable Manufacturing in Transportation, 2024)
Multidimensional decision-making issues invariably entail a profusion of factors and dimensions necessitating consideration. In such intricate environments, decision-making can be notably challenging. To navigate this complexity, the realm of multiple criteria decision-making approaches is indispensable, helping in unraveling convoluted predicaments. This paper introduces a novel approach fuzzy combinative multiple criteria decision-making analysis — crafted to address fuzzy decision analysis challenges. At the heart of this method lies the utilization of the Euclidean distance as the primary measure and the rectilinear distance as the secondary measure, both calibrated in accordance with the negative-ideal solution. Determining the desirability of alternatives rests on these distances. Further augmenting the evaluation, the process involves combining the Euclidean and rectilinear distances through fuzzy combinative multiple criteria decision-making analysis. The efficacy and stability of the fuzzy decision analysis are underscored through a numerical example, illustrating the proposed method’s procedural nuances. A comparative analysis comparing both Euclidean distance and rectilinear distance with the weighted sum model and the weighted product model is also conducted. This scrutiny underscores the efficiency of the proposed method while affirming the reliability of its outcomes.